2016
DOI: 10.1111/1365-2664.12792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of controlled neonicotinoid exposure on bumblebees in a realistic field setting

Abstract: 1. Pesticide exposure has been implicated as a contributor to insect pollinator declines. In social bees, which are crucial pollination service providers, the effect of low-level chronic exposure is typically non-lethal leading researchers to consider whether exposure induces sub-lethal effects on behaviour and whether such impairment can affect colony development. 2. Studies under laboratory conditions can control levels of pesticide exposure and elucidate causative effects, but are often criticised for being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 59 publications
1
56
0
Order By: Relevance
“…We made the assumption that spiking the sucrose solution with the neonicotinoid would not deter feeding if given no other option, as supported by pilot observations and previous studies (Arce et al, 2017;Gill et al, 2012;Kessler et al, 2015). Our pilot study also indicated that workers took a mean (±SEM) duration of 50 ± 13 s to commence feeding, defined as prolonged (>2 s) proboscis extension on to the cotton wool, and fed for a mean (±SEM) duration of 213 ± 24 s before stopping, with subsequent feeds being rare, sporadic, and short (<10 s).…”
Section: Methodsmentioning
confidence: 99%
“…We made the assumption that spiking the sucrose solution with the neonicotinoid would not deter feeding if given no other option, as supported by pilot observations and previous studies (Arce et al, 2017;Gill et al, 2012;Kessler et al, 2015). Our pilot study also indicated that workers took a mean (±SEM) duration of 50 ± 13 s to commence feeding, defined as prolonged (>2 s) proboscis extension on to the cotton wool, and fed for a mean (±SEM) duration of 213 ± 24 s before stopping, with subsequent feeds being rare, sporadic, and short (<10 s).…”
Section: Methodsmentioning
confidence: 99%
“…However, control workers learned to handle flowers efficiently after fewer learning visits. Arce et al (2016) placed B. terrestris nests out in an area of parkland for a 5-week period while also supplying them with sugar solution treated with 5 ppb of clothianidin. The volume of sugar solution provided was estimated to be half that which colonies typically consume over the course of the experiment.…”
Section: Colony-level Impact On Bumblebeesmentioning
confidence: 99%
“…There is strong evidence to associate pesticide use with bee population decline (Woodcock et al., ) and consequently with potential losses to pollination services and crop yields (Stanley & Raine, ; Stanley, Garratt, et al., ). At the colony level, pesticide exposure is associated with negative impacts on fitness‐determining traits that include colony initiation, colony growth, and reproductive output (Arce et al., ; Baron, Jansen, Brown, & Raine, ; Baron, Raine, & Brown, , ; Rundlöf et al., ; Tsvetkov et al., ; Whitehorn, O'Connor, Wackers, & Goulson, ; Woodcock et al., ). The mechanisms that underlie these effects remain unclear, but pesticides have been shown to negatively impact key aspects of worker performance including foraging efficiency and navigation ability (Feltham, Park, & Goulson, ; Gill & Raine, ; Gill, Ramos‐Rodriguez, & Raine, ; Henry et al., ; Stanley, Russell, Morrison, Rogers, & Raine, ).…”
Section: Introductionmentioning
confidence: 99%